2015
DOI: 10.14814/phy2.12273
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockout of smooth muscle sodium calcium exchanger type-1 lowers blood pressure and attenuates Angiotensin II-salt hypertension

Abstract: The functions of smooth muscle sodium calcium exchanger (NCX) in the vasculature are controversial and poorly understood. To determine the possible roles of NCX in the vascular phenotype and function, we developed a novel mouse model (SM‐NCX1 KO) in which the smooth muscle‐specific NCX type‐1 (NCX1) was conditionally knocked out using tamoxifen‐inducible Cre‐loxP recombination technique. SM‐NCX1 KO mice exhibit significantly lower blood pressure and attenuated angiotensin II (Ang II)‐salt‐induced hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…In earlier studies, we observed that MT and MR were correlated directly with basal BP in ␣ 2 ϩ/Ϫ mice (57) and in mice with SM-specific KO (53,58) and SM-specific overexpression (18) of NCX1 (NCX1 SM-KO and NCX1 SM-Tg , respectively). This, plus the aforementioned reasoning about Ca 2ϩ homeostasis and the reported association between arterial tone in vivo and in isolated arteries (8), led us to anticipate that MR might be inversely correlated with arterial ␣ 2 -Na ϩ pump ex- pression.…”
Section: Mr Does Not Correlate With Sm-specific Expression Of ␣ 2 -Namentioning
confidence: 89%
See 3 more Smart Citations
“…In earlier studies, we observed that MT and MR were correlated directly with basal BP in ␣ 2 ϩ/Ϫ mice (57) and in mice with SM-specific KO (53,58) and SM-specific overexpression (18) of NCX1 (NCX1 SM-KO and NCX1 SM-Tg , respectively). This, plus the aforementioned reasoning about Ca 2ϩ homeostasis and the reported association between arterial tone in vivo and in isolated arteries (8), led us to anticipate that MR might be inversely correlated with arterial ␣ 2 -Na ϩ pump ex- pression.…”
Section: Mr Does Not Correlate With Sm-specific Expression Of ␣ 2 -Namentioning
confidence: 89%
“…In the latter, basal BP correlated directly with arterial NCX1 expression (18,53,58) (Figs. 3 and 4), whereas basal BP is reduced in ␣ 2 SM-Tg mice even though NCX1 is overexpressed (Fig.…”
Section: Pumpsmentioning
confidence: 93%
See 2 more Smart Citations
“… b ; Wang et al . ). We infer that the EO‐induced, α2‐mediated increase in arterial NCX1 and SERCA2 expression, observed in many types of hypertension (Blaustein & Hamlyn, ; Blaustein et al .…”
Section: Introductionmentioning
confidence: 97%